REGISTER DRIVER MAXIM DALAM GRUP WHATSAPP “PASUKAN ANTI SAMBAT - Wa Ode Halfian; Asmariani Asmariani; Ashmarita Ashmarita (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
The purpose of this study is to describe the forms of the register used by Maxim drivers in the WhatsApp group “Pasukan Anti Sambat.” The method used in this research is a qualitative descriptive method. This type of research is field research. The data collection process involves reading, observing, taking screenshots, interviewing, and note-taking techniques. The data in this study consist of conversational texts containing registers sourced from the utterances of Maxim drivers in the WhatsApp group Pasukan Anti Sambat. The results of this study indicate that there are 18 registers categorized based on the linguistic units they form, which include (1) single forms, totaling 4 data; (2) complex forms, consisting of 3 data formed through affixation, 2 data formed through compounding, 4 data formed through abbreviation (acronyms), and 3 data formed through shortening; and (3) phrases, totaling 2 data.